The Effect of Religious Orientation on Students' Prosocial Behavior - Kurniawan, Khamdan; Japar, Muhammad; Purwanto, Edy (Universitas Negeri Semarang, 2023)
Prosocial behavior is urgent due to individual’s concerning behavior in today’s era. Violence, fight, abuse, and bullying are some phenomena which indicate someone has low prosocial behavior. The aim of this study was to prove whether religious orientation can affect prosocial behavior. It used a correlational design and involved 210 students of class XI. Findings revealed that religious orientation affected the increase in students’ prosocial behavior. Thus, students’ religiosity needs to be enhanced to boost the development of prosocial behavior.